2016
DOI: 10.1021/acs.langmuir.6b02229
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Molecular Dynamics Study of the Effects of Surface Hydrophilicity on Protein Adsorption

Abstract: The adsorption of streptavidin is studied on two surfaces, graphite and titanium dioxide, using accelerated molecular dynamics. Adsorption on graphite leads to strong conformational changes while the protein spreads out over the surface. Interestingly, also adsorption on the highly hydrophilic rutile surface induces considerable spreading of the protein. We pin down the cause for this unfolding to the interaction of the protein with the ordered water layers above the rutile surface. For special orientations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…Normally, proteins tend to adsorb on the hydrophobic or rough surface . While, our results and the earlier work from our lab showed that surface morphology played more important role in the rhBMP‐2 adsorption .…”
Section: Discussionsupporting
confidence: 57%
“…Normally, proteins tend to adsorb on the hydrophobic or rough surface . While, our results and the earlier work from our lab showed that surface morphology played more important role in the rhBMP‐2 adsorption .…”
Section: Discussionsupporting
confidence: 57%
“…The lysozyme molecule was placed ~10 Å above the PVDF membrane. Considering the large size and structural heterogeneity of lysozyme, different initial orientations of the lysozyme were considered, since it is well‐acknowledged that initial orientation affects adsorption behavior 55,56 . Regarding capturing representative orientations, an earlier study suggested 90° orientations 57 .…”
Section: Methodsmentioning
confidence: 99%
“…. The emission quenched ratio ( I 0 / I ) vs the concentration of Lys gave a Langmuir type curve (Figure B) . It was a good verification of adsorption of proteins onto the nanoparticles, resulting in the modulation of assembly of AIE state and the “switch‐off” of red emission.…”
Section: Resultsmentioning
confidence: 76%